(xy^2 + x - 2y + 3) dx + x^2 ydy = 2(x+y) dy

# DE Order one: (xy^2 + x - 2y + 3) dx + x^2 ydy = 2(x + y) dy

## New forum topics

- strength of materials: normal stress of hollow circular tube
- Please help me solve this problem: Moment capacity of a rectangular timber beam
- Solid Mensuration: Prismatoid
- Differential Equation: (1-xy)^-2 dx + [y^2 + x^2 (1-xy)^-2] dy = 0
- Differential Equation: y' = x^3 - 2xy, where y(1)=1 and y' = 2(2x-y) that passes through (0,1)
- Tapered Beam
- Vickers hardness: Distance between indentations
- Time rates: Question for Problem #12
- Make the curve y=ax³+bx²+cx+d have a critical point at (0,-2) and also be a tangent to the line 3x+y+3=0 at (-1,0).
- Minima maxima: Arbitrary constants for a cubic

$(xy^2 + x - 2y + 3)\,dx + x^2y\,dy = 2(x + y)\,dy$

$(xy^2 + x - 2y + 3)\,dx + (x^2y - 2x - 2y)\,dy = 0$

$\dfrac{\partial M}{\partial y} = 2xy - 2$

$N = x^2y - 2x - 2y$

$\dfrac{\partial N}{\partial x} = 2xy - 2$

Hence, the given is an exact equation

$\partial F = M \, \partial x$

$F = (xy^2 + x - 2y + 3)\,\partial x$

$F = \frac{1}{2}x^2y^2 + \frac{1}{2}x^2 - 2xy + 3x + f(y)$

$\dfrac{\partial F}{\partial y} = x^2y - 2x + f'(y)$

$\dfrac{\partial F}{\partial y} = N$

$x^2y - 2x + f'(y) = x^2y - 2x - 2y$

$f'(y) = -2y$

$f(y) = -y^2$

Thus,

$F = \frac{1}{2}x^2y^2 + \frac{1}{2}x^2 - 2xy + 3x - y^2$

$F = c$

$\frac{1}{2}x^2y^2 + \frac{1}{2}x^2 - 2xy + 3x - y^2 = c$

answer